Achieving reactive species specificity within plasma‐activated water through selective generation using air spark and glow discharges. Issue 8 (23rd January 2017) - Lu, Peng; Boehm, Daniela; Bourke, Paula; Cullen, Patrick J.
Abstract : Plasma‐activated liquids (PAL) attract increasing interest with demonstrated biological effects. Plasma exposure in air produces stable aqueous reactive species which can serve as chemical diagnostics of PAL systems. Here, we tailor aqueous reactive species inside plasma‐activated water (PAW) through treating water with AC air spark and glow discharges in contact with water. Chemical probing demonstrated species specificity between two types of PAW. Spark discharge PAW contains H 2 O 2 and N O 3 −, while N O 2 − and N O 3 − are generated in glow discharge PAW. Species formation in different PAWs have been discussed in terms of discharge mechanisms and liquid phase chemistry process. Species specificity can provide richer parametric spaces for producing PALs with controlled impact and dosage achievable by combining discharge modes or mixing different PALs. Abstract : We present a study on tailoring aqueous reactive species for plasma‐activated water (PAW) by treating deionized water with air spark and glow discharges in contact with water. Spark discharge PAW contains H 2 O 2 and N O 3 −, while N O 2 − and N O 3 − are generated in glow discharge PAW. Species specificity can provide richer parametric spaces for producing PALs with controlled impact and dosage achievable.